Shelley and the death drive: Romanticism, politics, psychoanalysis. Issue 5 (4th May 2021) - Hewitt, Ben
ABSTRACT: Psychoanalysis has strong roots in Romanticism, and Percy Bysshe Shelley's writings have often been thought to prefigure aspects of psychoanalytic theory. This essay explores affinities between Shelley's poetry and one particular concept: the 'death drive', or Thanatos, as Freud sometimes named it, counterpart of Eros in Freud's metapsychology. Freud felt that this controversial dualistic idea had literary support, writing that it is 'reinforced by our poets and playwrights'. My essay examines links between Shelley's writings, Freud's ideas, and their development in Lacanian theory, to ask whether Shelley provides such reinforcement for psychoanalytic metapsychology, especially in Alastor; or, the Spirit of Solitude (1816). Alastor, I argue, initiates a poetic probing of human psychology on Shelley's part which takes on a vitally political significance, creating a tension in Shelley's work between a utopianism and certain proto-psychoanalytic insights that seem to undermine it. With reference to A Philosophical View of Reform, 'Sonnet: Political Greatness', Prometheus Unbound, Hellas and The Triumph of Life, I conclude with some further reflections on the dialogue between Shelley and psychoanalysis, highlighting important implications of this for our understanding of Shelley's writings, and for our thinking about the relationships between Romanticism, politics and psychoanalysis.